(untitled) (Jurnal Bawaslu Provinsi Kepulauan Riau, 2024)
General elections are an important method of channeling people’s aspirations and are a key pillar in today’s democratic system. Indonesia will hold simultaneous elections in 2024, but the elections taking place this year are certainly not free from obstacles and challenges, one of which is the ethical problems faced by election organizers. DKPP has a key role in enforcing the code of ethics of election organizers to ensure democratic elections. This research emphasizes the urgency of enforcing the code of ethics and behavior of election administrators as well as the need for strategies and innovations, with a juridical-normative research method. The results show that the enforcement of KEPP is very important to maintain the independence, integrity and credibility of election organizers in order to create democratic and legitimate elections. Strategies and innovations in KEPP enforcement, including prevention, prosecution, and information technology, are needed for the effectiveness of organizing the 2024 national simultaneous elections. Keywords: Code of Ethics; Code of Conduct; General Election; Election Law; Regional Elections